Microbially Induced Calcite Precipitation (MICP) Biostimulation Increases Slope Safety Factor on Low Plasticity Soils - Ali, Mahardi Kamalika Khusna; Candra, Agata Iwan; Rayhansah, Rina Rebut (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
Low-plasticity clay (CL) soils are commonly found in tropical regions and generally have high water content, which reduces shear strength and lowers the slope safety factor (Fs). Conventional stabilization methods such as cement and fly ash are considered environmentally unfriendly because they produce high carbon emissions. Microbially Induced Calcite Precipitation (MICP) has emerged as a sustainable alternative for enhancing soil strength through the formation of biologically induced calcite. However, most previous MICP studies on slopes have focused on sandy soils, erosion control, and bioaugmentation. Therefore, it is necessary to investigate the application of Biostimulated MICP on high-moisture CL soils that represent tropical conditions and their relationship with slope Fs. This study aims to evaluate the effectiveness of biostimulated MICP on the stability of high-moisture CL soil slopes. Small-scale slopes were created in boxes with a 60° angle using the air pluviation method. The biostimulation solution used included urea, CaCl?, CH?COONa, NaOH, and sugarcane molasses to activate indigenous urease-producing bacteria. Testing included direct shear tests and slope-model loading tests with incubation times of 0 and 7 days. Fs analysis used an infinite-slope approach under steady-state seepage conditions. The results showed a 90.15% increase in cohesion and a 37.05% increase in internal friction angle, thereby increasing Fs to 88.72% after 7 days of MICP treatment. The results of the slope loading test showed a 105.41% increase in slope bearing capacity. These results indicate that the increase in cohesion and friction angle due to MICP is reflected in the slope's load-carrying capacity and in an increase in the Fs value. The findings indicate that biostimulated MICP has the potential as a sustainable slope stabilization technique and is suitable for tropical soil conditions.